Antiseptic Body Washes for Reducing the Transmission of Methicillin-Resistant Staphylococcus aureus: A Cluster Crossover Study. (17th April 2015) - Harris, Patrick N. A.; Le, Bich Diep; Tambyah, Paul; Hsu, Li Yang; Pada, Surinder; Archuleta, Sophia; Salmon, Sharon; Mukhopadhyay, Amartya; Dillon, Jasmine; Ware, Robert; Fisher, Dale A.
Abstract : In a cluster cross-over trial, targeted decolonization with octenidine body washes was not associated with reduction in MRSA transmission or infection Abstract: Background. Limiting the spread of methicillin-resistant Staphylococcus aureus (MRSA) within healthcare facilities where the organism is highly endemic is a challenge. The use of topical antiseptic agents may help interrupt the transmission of MRSA and reduce the risk of clinical infection. Octenidine dihydrochloride is a topical antiseptic that exhibits in vitro efficacy against a wide variety of bacteria, including S aureus . Methods. We conducted a prospective cluster crossover study to compare the use of daily octenidine body washes with soap and water in patients identified by active surveillance cultures to be MRSA-colonized, to prevent the acquisition of MRSA in patients with negative screening swabs. Five adult medical and surgical wards and 2 intensive care units were selected. The study involved an initial 6-month phase using octenidine or soap washes followed by a crossover in each ward to the alternative product. The primary and secondary outcomes were the rates of new MRSA acquisitions and MRSA clinical infections, respectively. Results. A total of 10 936 patients admitted for ≥48 hours was included in the analysis. There was a small reduction in MRSA acquisition in the intervention group compared with controls (3.0% vs 3.3%), but this reduction was not significant (odds ratio, 0.89; 95% confidence interval, .72–1.11; P = .31). There were also no significant differences in clinical MRSA infection or incidence of MRSA bacteremia. Conclusions. This study suggests that the targeted use of routine antiseptic washes may not in itself be adequate to reduce the transmission of MRSA in an endemic hospital setting.